Projeto remição pela leitura: a contribuição literária na formação de leitoras no centro de recuperação feminino de Santarém - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
This work presents a study on the literary contribution in the formation of female readers in the center for women's recovery in Santarém, with emphasis on the application of the Remição pela Leitura project, an initiative of the National Council of Justice (CNJ) and sponsored by the states. The project was undertaken in the Santarém prisons, where education in prisons also works, in the form of Youth and Adult Education (EJA). It is pointed out how the Redemption by Reading project contributes to the literary reading formation within the prison for women deprived of their liberty. In the development of the work, a bibliographic research was carried out, with access to material produced by the interns participating in that project. We verified the results in the development of reviews that assure the inmates the right to remission of sentence, that is, reduction of 4 days of their prison time to be served, per work read and reviewed, with a limit of up to 12 works per year, or 48 days/year. The work is accompanied by a teacher from the public state school system. Within this context, we seek to verify aspects related to the work of teaching in prison, the challenges and advances of teaching the formation of literary readers, taking into account conditions of physical structure, logistics, bibliographic collection and even the level of training of the project participants. The time frame for the research was the year 2021; The theoretical references used to support this study are based on COSSON (2009), which deals with the formation of the literary reader; FREIRE (2011) who develops the thesis that reading is transformative and liberating, ensuring the reader's autonomy; and CÂNDIDO (2011) which discusses the importance of literature and as a right for every person. The results indicated, according to the research, are of autonomy in thinking about the construction of arguments and in the development of ideas in the newsrooms, expressing a significant advance in the reading and argumentative capacity, verified in the results obtained in the research, guided by the question: working with the Does literary reading in women's prisons contribute to the citizen formation of female prisoners?
Keywords: Leitor literário; Remição de pena pela leitura; Mulheres privadas de liberdade; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE